Analysis of Science Literacy-Based High School Physics Textbooks using Weight Product Methods - Dewi, Novi Ayu Kristiana; Andriani, Novita; Atmaja, Vincencius Bellin (FKIP Universitas Lampung, 2022)
This study aims to determine the best science literacy-based physics textbook. This research is a descriptive study with data analysis techniques using the weight product method as a decision support system. The research sample comprised eleven high school physics textbooks for class X in Lampung Province. Methods of collecting data through observation, interviews, documentation, and questionnaires. Based on the research, the selection of the best science literacy-based physics textbook is made using the weight product method with the following steps: determining the criteria, making a suitability rating between alternatives and criteria, determining the weight of each criterion and its normalization, calculating the S value as an alternative preference, calculating the V value as a final alternative preference for ranking. Based on the final calculation results, the best alternative high school physics textbook based on science literacy was obtained with a value of V = 0.1070, namely B11. Keywords: textbook, scientific literacy, weight product method, decision support. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.1296-1307